Is there a role for tapered topical dose steroidal treatment for dry eye disease? A randomized, pilot study. Issue 4 (July 2022) - Barabino, Stefano; Montaldo, Elisa; Mingari, Maria Cristina; Mazzotta, Cosimo; Giuffrida, Sebastiano; Rolando, Maurizio
Purpose: To evaluate the effect of tapered doses of loteprednol-etabonate in dry eye disease patients. Materials and methods: Dry eye and treatment outcomes were assessed by Schirmer I test, tear BUT, lissamine green conjunctival staining, fluorescein corneal staining, and HLA-DR expression on conjunctival cells. Patients received either loteprednol-etabonate 0.5% twice daily for 14 days tapered to once daily for 14 days, and then twice weekly for 28 days ( n = 10), or NaCl 0.9%. Results: A significant decrease of ocular surface inflammation and improvement of symptoms was recorded in the study group compared with controls at days 14 and 56. Change from baseline in HLA-DR expression in CD45+ conjunctival cells was significantly higher in treated patients at day 14. Intraocular pressure and best corrected visual acuity were preserved in all treated eyes. Conclusions: Tapered doses of loteprednol etabonate 0.5% suspension controlled ocular surface inflammation, improving dry eye symptoms.